PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KETERLAMBATAN PENGIRIMAN BARANG DALAM TRANSAKSI BELANJA ONLINE - Risna Ratna Ayu (2022)
ABSTRACT Trade activities in Indonesia from time to time are growing rapidly. With the online (e-commerce) shopping activity, there was a doubling of spike during the Covid-19 disease outbreak. But behind the many consumer interests and the success of online shopping applications, there are still many weaknesses that cause harm to consumers. Therefore, consumers get legal protection against rules related to online shopping transactions.The research method used in this research is qualitative juridical which is based on legal norms contained in various laws and regulations regarding Consumer Protection and court decisions related to Electronic Information and Transactions. The data collection technique is through literature study and data sources. The results of this study indicate that there are often obstacles in the process of buying and selling online, especially in the delay in delivery of goods which is one of the problems that often occurs. As a result, consumers often feel disadvantaged due to problems with shipping goods. The business actor provides compensation for the loss suffered by the consumer in the case of loss or damage in accordance with the value of the goods. The conclusion of solving problems that occur in legal protection for consumers for delays in delivery of goods in online shopping transactions requires accountability that occurs between consumers and sellers during the covid-19 period. Keywords: Consumer protection, Delays in delivery, E-commerce